Clinicopathological profile and outcome of COVID-19 infection among children and newborn admitted to a dedicated COVID hospital in West Bengal, India - Bose, Some Suvra; Khemani, Poonam; Khemka, Arpita; Ghosh, Ananya; Mondal, Rakesh (International Journal Of Community Medicine And Public Health, 2020)
Background: Aim of the study was to assess the clinicopathological profile and outcome of COVID 19 infection in children and newborn in a dedicated COVID tertiary care center. Methods: A retrospective study of a cohort of 105 children (1 month-12 years.) and 128 newborns admitted from 7th July to 7th August 2020. All the admitted children were COVID 19 positive and newborns were delivered from mother with COVID positive status. We collected data from medical records regarding epidemiology, clinical features, comorbidities, investigational report, treatment and outcome of the study population. Results: The median age of 105 children was 3 years with IQR (11 months-6 years) with almost equal sex distribution with higher disease prevalence and severity in younger age group. The mean duration of stay is 10.11 days (SD: 4.93). 35 (33.3%) children were asymptomatic, whereas 53 (50.5%) mildly symptomatic, 8 (7.6%) moderate disease severity, 9 (8.6%) critically ill at time of admission. Fever (57%) and Cough (23.8%) commonest symptoms. Hyper inflammatory syndrome was a new challenge in COVID affected children as well as concomitant infections like Dengue, Scrub and enteric fever, 38 (56%) children had comorbidities and 14 (13.3%) required PICU admission with 4 (3.8%) children. 42 out of 128 neonates became positive being born from 128 COVID positive mother and the rate of longitudinal transmission was more in outborn babies. None of the newborns tested swab positive within 48hrs of life and the preterm and LBW babies were relatively less infected. Most of the neonates were asymptomatic (84%) and we recorded zero death among COVID positive newborn. Conclusions: In the absence of comorbidities and concurrent infections, COVID 19 is relatively benign in Indian children.